Comparing desferrioxamine and light fractionation enhancement of ALA-PpIX photodynamic therapy in skin cancer - de Souza, Ana Luiza Ribeiro; Marra, Kayla; Gunn, Jason; Samkoe, Kimberley S; Kanick, Stephen Chad; Davis, Scott C; Chapman, M Shane; Maytin, Edward V; Hasan, Tayyaba; Pogue, Brian W (British journal of cancer, 2016)
Background: Aminolevulinic acid (ALA)-based photodynamic therapy (PDT) provides selective uptake and conversion of ALA into protoporphyrin IX (PpIX) in actinic keratosis and squamous cell carcinoma, yet large response variations in effect are common between individuals. The aim of this study was to compare pre-treatment strategies that increase the therapeutic effect, including fractionated light delivery during PDT (fPDT) and use of iron chelator desferrioxamine (DFO), separately and combined. Methods: Optical measurements of fluorescence were used to quantify PpIX produced, and the total amount of PpIX photobleached as an implicit measure of the photodynamic dose. In addition, measurements of white light reflectance were used to quantify changes in vascular physiology throughout the PDT treatment. Results: fPDT produced both a replenishment of PpIX and vascular re-oxygenation during a 2 h dark interval between the first and second PDT light fractions. The absolute photodynamic dose was increased 57% by fPDT, DFO and their combination, as compared with PDT group (from 0.7 to 1.1). Despite that light fractionation increased oedema and scab formation during the week after treatment, no significant difference in long-term survival has been observed between treatment groups. However, outcomes stratified on the basis of measured photodynamic dose showed a significant difference in long-term survival. Conclusions: The assessment of implicit photodynamic dose was a more significant predictor of efficacy for ALA-PDT skin cancer treatments than prescription of an enhanced treatment strategy, likely because of high individual variation in response between subjects.